Bid-ask spread determinants and characteristics of Euroyen futures contracts on the SIMEX - Teo, Hong Hong (2014)
The purpose of this report is to give an insight to the determinants of bid-ask spreads and the characteristics of Euroyen futures contracts traded on the Singapore International Monetary Exchange (SIMEX). Previous studies on this topic concentrate mainly on the equity market. This report extends the analysis to the futures market, in particular the three-month Euroyen futures contracts. Data from the SIMEX is utilized for the analysis. A multiple linear regression is done on the determinants of bid-ask spread which are namely, risk, information and volatility. Dummy variables are also included to capture the effect of different time intervals and the day-of-the-week. The results show a positive correlation with information and a negative correlation with volatility and activity level. In addition, Fridays and the period from 1800hrs to 1830hrs are separately found to be the least costly time to trade.